Aubrey Beardsley, Venus und Tannhäuser - Benda, Wolfram (2016)

Charles Baudelaire, Die Qualen des Opiums - Benda, Wolfram (2012)

Charles Perrault, Blaubart - Benda, Wolfram (2015)

Charles Robert Maturin, Melmoths Traum. - Benda, Wolfram (2011)

Dominik Riedo, Wolf von Niebelschütz. Leben und Werk. Eine Biographie. - Benda, Wolfram (Arbitrium, 2015)

Gérard de Nerval, Constantinopel bei Nacht. - Benda, Wolfram (The Bear Press, 2015)

Gérard de Nerval, Constantinopel bei Nacht. - Benda, Wolfram (2015)

H. P. Lovecraft, Kosmische Fieberträume - Benda, Wolfram (2016)

Hugh Ludlow, Stunde & Macht der Finsternis - Benda, Wolfram (2012)

Hugo von Hofmannsthal, Der Tod des Tizian. The Bear Press Wolfram Benda, Bayreuth 2011. - Benda, Wolfram (The Bear Press, 2011)

Jean Paul und die Bilder. Bildkünstlerische Auseinandersetzungen mit seinem Werk: 1783 – 2013. Mitherausgeber Monika Schmitz-Emans. Königshausen-Neumann, Würzburg 2013. - Schmitz-Emans, Monika; Benda, Wolfram (Königshausen und Neumann, 2013)

John Keats, Im Bardenland - Benda, Wolfram (2011)

Joseph Conrad, Der Freibeuter. - Benda, Wolfram (2011)

Joseph Conrad, Jugend. - Benda, Wolfram (The Bear Press, 2016)

Joseph Conrad, Jugend - Benda, Wolfram (2016)

Paul Mersmann, Nachtfenster. - Benda, Wolfram (The Bear Press, 2013)

Shaftesbury (Anthony Ashley Cooper): Band II,6: Askemata I (Englisch) - Müller, Patrick; Benda, Wolfram; Jackson-Holzberg, Christine; Uehlein, Friedrich; et al. (Frommann-Holzboog, 2011)
Die ›Askêmata‹ dokumentieren Shaftesburys »Studdy of Happiness«, die Einübung in ein philosophisches Leben. Sie wurden größtenteils in Zeiten des äußeren und inneren Rückzugs aus dem öffentlichen Leben verfasst; allgegenwärtig sind die Vorbilder Epiktet und Marc Aurel. Mittels philosophischer Selbstanalyse versucht Shaftesbury, eine auf das Wesentliche konzentrierte Grundeinstellung zu finden, deren praktische Umsetzung allein zur Tugend, zur wahren »Happiness« führen kann. Der Text wird hier erstmals vollständig kritisch ediert; neben einer Einleitung und Erläuterungen findet sich in dem Band noch ergänzendes Material aus dem Nachlass.

Shaftesbury, Standard Edition, Band II,6, Askemata, - Benda, Wolfram; Jackson-Holzberg, Christine; Müller, Patrick; Uehlein, Friedrich (frommann-holzboog, 2011)
Almost all volumes (one exception: II 3) contain photographic reproductions of the emblematic engravings commissioned by Shaftesbury for the second edition of his Characteristicks; some of our texts are also accompanied by plates showing the original manuscript or an editio princeps. Eds Wolfram Benda, Christine Jackson-Holzberg, Patrick Müller, Friedrich A. Uehlein. 57-470: Shaftesbury’s manuscript Askêmata. 471-543: six appendices showing related and for the most part previously unpublished manuscript texts: a fragment on Oikonomia; the “Parchment” (a personal pocket encheiridion); Excerpta; Laws; the “Prayer”; Dogmata. A new and annotated critical edition of the Earl’s philosophical exercises or “Closet-Work”: the “Studdy Writing Figuring Practicing” necessary to “the Work of Self-Improvement”.

Sir Thomas Browne, Die Rose des Paracelsus - Benda, Wolfram (2011)

Thomas de Quincey, Orientalische Nachtmahre - Benda, Wolfram (2013)

William Beckford, Sturm über Neapel - Benda, Wolfram (2015)

Zauberspiegel. Jean Paul und Stephan Klenner-Otto sowie ein Exkurs über Jean Paul und die Buchkunst. - Benda, Wolfram (Jean Paul und die Bilder. Bildkünstlerische Auseinandersetzungen mit seinem Werk: 1783 – 2013., 2013)